Sistem Monitoring Instrument Air System Berbasis Internet Of Things di PT.Parna Raya - Nurfaizi, Akhmad; Sulistiyowati, Indah (Department of Electrical Engineering, Faculty of Engineering, Universitas Lampung, 2022)
There is an operation process for facility & equipment support in the distribution process of the oil and gas company such as the Pressure Regulating System and Process Shutdown Valve. The supporting equipment uses pneumatic actuators as a driving force whose power source comes from air, as from the fact the compressor as an air producer is still manually used and the air pressure in the air receiver is not monitored from the control room. The purpose of this research is to develop the previous system by creating an integrated system that can be monitored remotely in real time by adding several electronic devices and utilizing Internet of Things technology. Based on the research that have been carried out, the pressure sensor has good accuracy with an average error of 0.06 percent, so it can be a reference in monitoring the pressure on the air receiver and a notification alarm will appear if the pressure on the air receiver reads 5.5 Bar as evidenced by testing 10 times the average pressure read on the blynk app of 5,460 Bar. Hardware and software function properly according to the design, air pressure at the air receiver and status of the compressor in stand-by or running state can be monitored through the blynk app, so that the gas distribution process does not stop again